2018
DOI: 10.3221/igf-esis.47.35
|View full text |Cite
|
Sign up to set email alerts
|

Timber beam seismic design – A numerical simulation

Abstract: In order to design a seismic timber beam, the effect of near-fault ground motion on timber beam has numerically been investigated, with reference to small displacement theory. The simulated near-fault ground motion is applied on the fixed base of a timber frame model. The beam is placed in single span of a timber frame. The beam has two different length sizes of 1.8 and 3.3 meters. The seismic load-displacement, seismic load-strain and strain-displacement have been calculated for all models and shown in graphs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The investigation was to understand the timber frame seismic response as the timber frame is subjected to near‐fault ground motion. In the numerical analysis, the ABAQUS software was used for the seismic design of a timber frame shown in Figure . Figure A shows near‐fault ground motion is applied to the single‐span timber frame.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The investigation was to understand the timber frame seismic response as the timber frame is subjected to near‐fault ground motion. In the numerical analysis, the ABAQUS software was used for the seismic design of a timber frame shown in Figure . Figure A shows near‐fault ground motion is applied to the single‐span timber frame.…”
Section: Discussionmentioning
confidence: 99%
“…In the numerical analysis, the ABAQUS software was used for the seismic design of a timber frame shown in Figure 1. 1 Figure 2A shows near-fault ground motion is applied to the single-span timber frame. Figure 2B shows near-fault ground motion zoomed from 22 to 26 seconds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a report on the improvement of the seismic resistance of historical industrial timber buildings [4]. Several research were reported on timber beam and column to study displacement, strain energy and seismic load sharing [5][6][7].…”
Section: Introductionmentioning
confidence: 99%